Iklim sekolah di SMP negeri kecamatan koto tangah padang - Melani; Sabandi, Ahmad; Nellitawati; Ermita (Journal of Practice Learning and Educational Development, 2023)
This study aims to find out (1) to describe the school climate towards staff freedom at the Koto Tangah Padang District Public Middle School, (2) to describe the school climate towards professional interest at the Koto Tangah Padang District Public Middle School, (3) to describe the school climate towards affiliation at the Public Middle School Koto Tangah Padang District, (4) describes the school climate towards support for students at SMP Negeri Koto Tangah Padang District, (5) describes the school climate towards the completeness of resources at SMP Negeri Koto Tangah Padang District. This type of research is descriptive research. The population in the study were teachers at the Koto Tangah Padang District Public Middle School, totaling 72 samples. Sampling using stratified proportional random sampling technique. The instrument used for research is a closed questionnaire using descriptive analysis. The results showed that: (1) the school climate towards staff freedom at the Koto Tangah Padang District Public Middle School was conducive with the highest average of 4.6, (2) the school climate towards professional interest at the Koto Tangah Padang District Public Middle School was very conducive with an average the highest average is 4.75, (3) the school climate towards affiliation at the Koto Tangah Padang District Public Middle School is conducive with the highest average 4.54, (4) the school climate towards supporting students at the Koto Tangah Padang District Public Middle School is very conducive with the highest average is 4.75, (5) the school climate for the completeness of resources at SMP Negeri Koto Tangah Padang District is very conducive with the highest average being 4.67. The conclusion is that the school climate in SMP Negeri Koto Tangah Padang District is conducive from all aspects, namely from staff freedom, professional interest, affiliation, support for students and to the completeness of resources.